Strategies for Rebranding in the New Era of Institutes under The Office of the Vocational Education Commission - Taraartorn, Napaporn; Nuntee, Sakdinaporn; Bangwiset, Suchat (Journal of Education Studies, Chulalongkorn University, 2024)
The objectives of this research were to: 1) study the components of rebranding in the new era of institutes under the Office of the Vocational Education Commission; 2) study the current, desirable conditions and needs of rebranding; and 3) create and develop strategies for rebranding. The research procedures were divided into three phases. Phase 1 involved determining the requisite components by examining documents and interviewing nine experts. Phase 2 involved studying the current, desirable conditions and needs of rebranding; the sample included 390 administrators and teachers. Phase 3 involved creating and developing strategies through a focus group discussion with nine experts, followed by evaluating the strategies with a group of nine experts. The instruments used were semi-structured interviews, questionnaires, and strategy evaluation. The statistical methods used consisted of percentage, mean, standard deviation, and modified PNI. The results showed that: 1) there were 5 components to rebranding, which consisted of placing an administrator in the new era, teachers and education personnel in the new era, learners in the new era, institutional operations in the new era including institutional social responsibility; 2) the current conditions were found to be at a high level, desirable conditions were at the highest level, and the greatest needs of rebranding was learners in the new era; 3) the strategies consisted of a vision, five missions, five goals, five strategic issues, 21 strategies, 54 measures, and 47 indicators, and the evaluation of strategies was found to be at the highest level of utility, suitability, and possibility.